Spectrophotometric Determination of Amoxicillin Using New Organic Reagent via Different Analytical Methods - Helen Abd Alhassan Mahmood; Rulla Sabah; Nisreen Kais Abood (Indonesian Journal of Chemistry, 2023)
New and simple spectrophotometric method was applied for amoxicillin determination by oxidative coupling with an organic reagent 1-(4-aminophenyl)-3-(5-(4-nitrophenyl)-furan-2-yl)-yl)-prop-2-en-1-one (H) to form an orange colored dye with λmax of 490 nm. The molecular structure of the new compound H was characterized using spectral analysis including 1H-NMR, FTIR, Mass spectroscopy, and UV-visible. The concentration range of oxidative coupling obeyed Beer's law was 2–50 μg/mL, the correlation coefficient was 0.9995, molar absorptivity was 0.63 × 104 L/mol cm, and the detection limit was 0.189 μg/mL. The concentration range of flow injection obeyed Beer's law was 1–150 μg/mL, the correlation coefficient was 0.9994, molar absorptivity was 0.295 × 104 L/mol cm, and the detection limit was 0.407 μg/mL. The proposed method was successfully applied in pharmaceutical formulation for amoxicillin determination. The results showed that amoxicillin could be reacted with a new compound H in the alkaline medium in the presence of oxidative agent NaIO4 and automated by flow injection analysis. The proposed methods have the advantage of simple, fast, very sensitive, good precision and accuracy. The suggested technique was effectively used to estimate amoxicillin in both its pure form and pharmaceutical formulations.